(untitled) (Communications in Computational Chemistry, 2025)
The stereodynamics of the reaction H(^2S) + NH (v= 0, 1, 2, 3; j = 0)→N(^4S) + H_2 are studied using the quasi-classical trajectory method on a double many-body expansion potential energy surface to understand the alignment and orientation of the product molecules in the collision energy range of 2–20 kcal·mol^−1, The vibrational–rotational quantum number of the NH molecules is specifically investigated for v = 0, 1, 2, and 3 and j = 0. The P(θ_r), P(φ_r ), P(θ_r ,φ_r ), differential cross section [DCS; (2πσ)(dσ_00/dw_t)], and average rotational alignment factor 〈P_2(cosθ_r)〉 are calculated. The stereodynamics results indicate that the reagent vibrational quantum number and initial collision energy significantly affect the distributions of the k–j', k–k'–j' and k–k' vector correlations along with 〈P_2(cos θ_r)〉. In addition, while DCS is extremely sensitive to the collision energy, it is not significantly affected by the vibrational excitation of the reagents.